THE EFFECT RECOMBINANT GROWTH HORMONE (rGH) DOSES AND IMMERSION DURATION ON GROWTH AND SURVIVAL RATE OF RIVER CATFISH LARVAE (Hemibagrus nemurus) - Ika Riezki Ananda; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT            This research was conducted on February 16, 2020 - March 27, 2020, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Riau University. The aim of this research was to determine the effect ofRecombinant Growth Hormone (rGH) and the optimal dose and immersion duration on growth and survival rate of river catfish larvae (Hemibagrus nemurus). The method used  was a Completely Randomized Design Factorial with 2 factors. The first factor was  the dose of rGH with 4 levels;  0 mg/L (D0), 2,5 mg/L (D1), 3 mg/L (D2), and3,5 mg/L (D3). The second factor was the immersion duration with three levels of 45 minutes (P1), 60 minutes (P2) and 75 minutes (P3) respectively.The larvae were cultured preserved in jars for 40 days with 5 fish/L density. The results showed that the use of different doses and  immersion duration of rGH effected  on absolute weight, absolute length, specific growth and survival rate of river catfish larvae. Treatment dose 3 mg /L and 60 minutes (D2P2) with the result of absolute weight growth of 1.95 grams, absolute length 6.08 cm, specific growth rate of 15.88 % and survival rate of 84.66%. The water quality parameters during the study were optimal for river catfish larvae with temperature 27.8-28.9 oC, pH 5.9-6.9 and dissolved oxygen 3.5-6.8 mg/L.Keywords :Doses, Immersion Duration, Recombinant Growth Hormone,Hemibagrus nemurus.